Modified transurethral resection of the prostate (TURP) for men with moderate lower urinary tract symptoms (LUTS) before brachytherapy is safe and feasible. (15th December 2014) - Brousil, Philip; Hussain, Muddassar; Lynch, Mark; Laing, Robert W.; Langley, Stephen E.M.
Abstract : Objective: To report the urinary toxicity outcomes for patients at greater risk of voiding symptoms and retention who received a modified limited transurethral resection of the prostate (TURP) before low‐dose rate (LDR) brachytherapy. Patients and Method: Data were analysed from patients receiving the above procedures between 2006 to present, taken from the prospective brachytherapy database of 2000 patients at the St. Luke's Cancer Centre. The limited TURP (TURP BXT ) was performed at a median (range) of 64 (25–205) days before seed implantation with a median resection weight of 1.15 g. Selection criteria were based on patients with moderate lower urinary tract symptoms, poor flow or post‐void residual urine volume (PVR), or a prominent middle lobe or high bladder neck on transrectal ultrasonography. Baseline prostate cancer characteristics, uroflowmetry, International Prostate Symptom Score (IPSS) and quality‐of‐life QoL scores were collected and compared with follow‐up IPSS and QoL scores. Results: Data for 112 patients was gathered from the database. The TURP BXT resulted in statistically significant improvements before LDR brachytherapy in maximum urinary flow rate (Qmax ) and PVR, IPSS and QoL scores (the mean Qmax before vs after the TURP BXT was 11.3 vs 16.7 mL/s). The IPSS and QoL scores at 6 months after seed implantation were increased compared with baseline values before the TURP BXT (mean IPSS at 6 months 11.7 vs 9.2 before TURP BXT ), but no difference at 1 year (mean IPSS 9), and improved scores at 2, 3, 4 and 5 years follow‐up (mean IPSS of 7.9, 5.6, 5.3 and 7.4, respectively). Conclusion: The present study suggests patients at increased risk of deteriorating voiding symptoms, including urinary retention, are no longer contraindicated against LDR brachytherapy if they receive a modified TURP before seed implantation. This procedure does not appear to carry the risk of urinary incontinence thought to be associated with a conventional TURP before LDR brachytherapy.